Sternal Osteomyelitis Caused by Gordonia bronchialis after Open-Heart Surgery - Chang, Jeong-Hyun (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2014)
We report the case of a deep sternal wound infection with sternal osteomyelitis caused by Gordonia bronchialis after open-heart surgery. The isolate was identified as a G. bronchialis by 16S rRNA and hsp65 gene sequencing, having initially been misidentified as a Rhodococcus by a commercial phenotypic identification system.